2011
DOI: 10.1111/j.1365-3156.2011.02727.x
|View full text |Cite
|
Sign up to set email alerts
|

Trichuris and hookworm infections associated with anaemia during pregnancy

Abstract: Summaryobjective To assess the following associations between the second and third trimesters of pregnancy: (i) the intensity of soil-transmitted helminth (STH) infection and haemoglobin ⁄ anaemia, (ii) the effect of mebendazole treatment on the occurrence of STH infection, and (iii) the effect of mebendazole treatment on haemoglobin ⁄ anaemia.methods Data originated from a trial of 1042 pregnant women recruited in their second trimester and followed to delivery. Baseline assessments included socio-demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 23 publications
1
43
0
2
Order By: Relevance
“…[23][24][25] A recent study has also shown an adverse effect of T. trichiura infection as well as co-infection with hookworm and T. trichiura on maternal anemia. 26 Maternal hemoglobin may therefore be an appropriate surrogate marker of adverse birth outcomes. In studies one can control for iron supplementation, which may make it easier to detect an impact of the parasitic infections.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] A recent study has also shown an adverse effect of T. trichiura infection as well as co-infection with hookworm and T. trichiura on maternal anemia. 26 Maternal hemoglobin may therefore be an appropriate surrogate marker of adverse birth outcomes. In studies one can control for iron supplementation, which may make it easier to detect an impact of the parasitic infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies had differentiated between Trichuris infection intensity categories. Of the single study which had examined Trichuris infection intensity categories, results showed that pregnant women with moderate or heavy Trichuris infection in their second trimester of pregnancy had statistically significantly lower Hb levels compared to those with no or light Trichuris infection, despite all of the women receiving iron supplementation [16]. It, therefore, showed an association between both Trichuris infection and increasing Trichuris intensity, as well as an increased risk of anemia—and this despite iron supplementation.…”
Section: The Evidence Linking Soil-transmitted Helminths and Anemiamentioning
confidence: 98%
“…Moreover, there is limited evidence demonstrating that, in cases where there is co-infection of Trichuris with hookworm, the risk of anemia increases with increasing intensity of either Trichuris infection or hookworm infection [16]. However, more research is needed on this topic.…”
Section: The Evidence Linking Soil-transmitted Helminths and Anemiamentioning
confidence: 99%
“…An analysis of the baseline (second trimester) data for an randomized controlled trials investigating the effectiveness of de-worming and iron supplementation in a population of more than 1000 pregnant women living in and around Iquitos in the Peruvian Amazon showed that women with moderate-to-heavy intensities of both hookworm and Trichuris infection were more than twice as likely to concurrently have anemia as those with no or light infection. An analysis of the trial proper documented the effect of mebendazole and iron supplementation on anemia and on the presence and intensity of STH infections 75 . A clinical study conducted in Venezuela shows that intestinal parasitic infections, especially due to helminthes, increase anemia in pregnant women and the results of this are low pregnancy weight gain and intra uterine growth retardation, followed by low birth weight, with its associated greater risks of infection and higher perinatal mortality rates.…”
Section: Hookworm Infectionmentioning
confidence: 99%